Chronic Stress in Adolescents and Its Neurobiological and Psychopathological Consequences: An RDoC Perspective. (June 2017) - Sheth, Chandni; McGlade, Erin; Yurgelun-Todd, Deborah
The Research Domain Criteria (RDoC) initiative provides a strategy for classifying psychopathology based on behavioral dimensions and neurobiological measures. Neurodevelopment is an orthogonal dimension in the current RDoC framework; however, it has not yet been fully incorporated into the RDoC approach. A combination of both a neurodevelopmental and RDoC approach offers a multidimensional perspective for understanding the emergence of psychopathology during development. Environmental influence (e.g., stress) has a profound impact on the risk for development of psychiatric illnesses. It has been shown that chronic stress interacts with the developing brain, producing significant changes in neural circuits that eventually increase the susceptibility for development of psychiatric disorders. This review highlights effects of chronic stress on the adolescent brain, as adolescence is a period characterized by a combination of significant brain alterations, high levels of stress, and emergence of psychopathology. The literature synthesized in this review suggests that chronic stress-induced changes in neurobiology and behavioral constructs underlie the shared vulnerability across a number of disorders in adolescence. The review particularly focuses on depression and substance use disorders; however, a similar argument can also be made for other psychopathologies, including anxiety disorders. The summarized findings underscore the need for a framework to integrate neurobiological findings from disparate psychiatric disorders and to target transdiagnostic mechanisms across disorders.